Pengaruh Partisipasi Anggaran Pada Budgetary Slack dengan Self Esteem dan LOC Sebagai Variabel Pemoderasi - Agus Aditya Pramana Putra, Putu; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to determine the effect of budget participation on budgetary slack and whether self esteem and locus of control are able to moderate the effect of budget participation on budgetary slack in the Badung District OPD. The samples in this study were the Head of the OPD, the Head of the Subdivision of Finance, and the Head of the Planning & Program Subdivision at each Dinas in Badung Regency with a total of 101 respondents. The method of determining the sample uses a purposive sampling method and data collection using a questionnaire. Data were analyzed using Moderated Regression Analysis (MRA). Based on the results of this study indicate that budgetary participation has a positive effect on budgetary slack, self esteem can weaken the influence of budgetary participation on budgetary slack and locus of control is not able to moderate the influence of budgetary participation on budgetary slack. Keywords: Budget participation, budgetary slack, self esteem, LOC